IMPLEMENTASI METODE TOPSIS UNTUK SISTEM PENDUKUNG KEPUTUSAN DALAM PEMILIHAN PAKET FOTO PERNIKAHAN (Studi Kasus : Digital Art Bali) - Julyantari, Ni Komang Sri; Putri, Ni Made Dewi Kansa; Budiarta, Komang (Jurnal informasi dan komputer, 2023)
Marriage is something that every couple looks forward to. All preparations for the wedding are needed so that the bride and groom have a dream of a magnificent, memorable and unforgettable wedding. Wedding photo packages usually consist of the concept, service, facilities, price, duration of time. Currently, the other obstacle is the cost of the bride and groom. The problem that is often faced is that the bride and groom have minimal costs but want attractive results. Problems like this often make it difficult for brides-to-be when there is a lack of information that can be used as a reference in making decisions about wedding packages. The research that has been done is then proposed an analysis in the selection of wedding photo packages using the TOPSIS (Technique For Order Preference by Similarity to Ideal Solution) method. The TOPSIS process is a multi-criteria decision-making method whose final result is a recommendation or decision for the decision maker